Réponses

Meilleure réponse !
2014-04-11T19:02:04+02:00
A. 5x = 3x +3
5x - 3x = 3
2x = 3
x = 2/3

b. 8x = 12x + 4
8x-12x = 4
-4x = 4
x = -1

c. 4-7y = 10y
4 = 10y + 7y
17y = 4
y = 4/17

d. 7x + 1 = -4 - x
7x + x = - 4 -1
8x = -5
x = -5/8

e. 2+ 3x = 7- 3x
3x + 3x = 7 -2
6x = 5
x = 5/6

f. 5 + 6x = -x -9
5 + 9 = -x -6x
14 = -7x
x = -14/7 = -2

g. 11x + 3 = 8x + 7
11x - 8x = 7 -3
3x = 4
x = 4/3

h. 5,5x + 1,5 = 9x + 6
5,5x - 9x = 6 - 1,5
-4,5x = 4,5
x = -1

i. 7-3,3x = 2x - 9,7
-3,3x - 2x = -9,7 - 7
-5,3x = -16,7
x = 16,7/5,3

j. 5,1 - x = -8x + 1,7
- x + 8x = 1,7 - 5,1
7x = - 3,4
x = - 3,4/7